2012
DOI: 10.1007/s10661-012-2787-6
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of arsenic contamination in Peninsular Malaysia based on Centella asiatica and soil samples

Abstract: The first objective of this study was to provide data of arsenic (As) levels in Peninsular Malaysia based on soil samples and accumulation of As in Centella asiatica collected from 12 sampling sites in Peninsular Malaysia. The second objective was to assess the accumulation of As in transplanted C. asiatica between control and semi-polluted or polluted sites. Four sites were selected which were UPM (clean site), Balakong (semi-polluted site), Seri Kembangan (semi-polluted site) and Juru (polluted site). The As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In addition, the concentration ranges of As in this study were in agreement with those reported by Ong et al. () (9.38 to 57.05 μg/g), where researchers had collected soil samples from 12 sampling stations in Peninsular Malaysia.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the concentration ranges of As in this study were in agreement with those reported by Ong et al. () (9.38 to 57.05 μg/g), where researchers had collected soil samples from 12 sampling stations in Peninsular Malaysia.…”
Section: Resultssupporting
confidence: 92%
“…In Malaysia, metals contamination is affecting the quality of the plants with medicinal attributes (Ong, Wong, Tan, & Yap, ; Ong, Yap, Maziah, Suhaimi, & Tan, ), which warrants the need of heavy metals monitoring in the medicinal plants grown in the country. The main objective of this study was to determine the uptake of two metals–As and Sb–by A. barbadensis based on common metal contamination indices, enrichment factor (EF), index of geoaccumulation (Igeo), bioconcentration factor (BCF), and translocation factor (TF), by transplantation of the plants in soils of two selected sites in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Both data shows a remain high total concentration of arsenic allowed in water resources. According to Ong et al, none of the local vegetable samples showed levels greater than 2.00 μg/g of arsenic in Malaysia [10]. The arsenic contamination in Malaysia did not reach the level of concern to the public at that time.…”
Section: Introductionmentioning
confidence: 97%
“…However, studies focusing on the adverse effects of organic arsenic are limited (Kato et al, 2010;Hammid et al, 2013;Ong et al, 2013). PON1 is a lactonase cardio-protective enzyme that hydrolyses ox-LDL and prevents oxidation of LDL (Aviram et al, 1998;Hao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%